Non‐Interleaved Polarization‐Frequency Multiplexing Metasurface for Multichannel Holography. Issue 22 (19th August 2022) - Gou, Yue; Ma, Hui Feng; Wu, Liang Wei; Sun, Shi; Wang, Zheng Xing; Cui, Tie Jun
Abstract: In order to enhance channel capacity in modern wireless communications, diverse multiplexing techniques, such as polarization, frequency, and spatial multiplexing, are proposed and implemented. Here, a non‐interleaved polarization‐frequency multiplexing metasurface is proposed, which can realize independent controls of orthogonal linearly polarized or circularly polarized waves in two frequency bands to achieve four independent information channels. As a proof of concept, the metasurfaces that can independently realize four different polarized holographic images in two frequency bands are designed, simulated, and measured. The results show that two orthogonally polarized holographic images are achieved in each frequency band, respectively, which can be either linear or circular polarization. Benefitting from the advantages of non‐interleaved design, the proposed metasurfaces can reach not only high information capacity but also high information density by taking full use of the metasurface apertures. Abstract : A non‐interleaved polarization‐frequency multiplexing metasurface is proposed, which can realize independent controls of orthogonal linearly polarized or circularly polarized waves in two frequency bands to achieve four independent information channels, and the results are validated by using four‐channel holographic imaging. This design can simultaneously make full use of polarization and frequency resources to increase the information capacity of the metasurface.